Laughing with Sacred Things, ca. 1100-1350: A History in Four Objects - Jones, Peter J. A. ca. 20./21. Jh. (Church history, 2020)
Exploring the range of circumstances in which medieval Christians laughed with, against, at, and through religious topics, this article investigates four objects: an ivory cross, an ampulla of a saint's blood, a preaching codex, and a pilgrim's badge. While these objects are taken to illustrate a diversity of attitudes to religious humor, they are also, in light of recent work citing the productive power of medieval matter, scrutinized as agents in their own right. The article suggests two significant patterns. On the one hand, the objects point to laughter's use as a unique mode of spiritual practice. Through amusing miracles, through the provocative work of comic sermons, and through the playful humor of pilgrimage badges, Christians from the twelfth to the fourteenth centuries were able to use humor to relate to their faith in sophisticated and often counterintuitive ways. Yet as the four objects and their use also attest, these modes of comic relation were also subjected to clerical reduction and regulation. Harnessing the pedagogical potential of laughter especially, preachers, hagiographers, and clerics all worked to redirect more anarchic forms of religious humor toward functional ends. While tracing how laughter with Christian topics was increasingly encouraged, the article suggests that the price of this encouragement was that laughter was often brought into a more policed domain of orthodox Christian practice.